Joint involvement in Ochronosis - Biehl, Christoph; Thormann, U.; Madera, N.; Heiß, C.; Justus Liebig University Giessen (My University, 2016)
Introduction: Ochronosis is a metabolic disorder that is usually associated with the typical brown-black colored urine and retention of phenol complexes in sclera and skin. Kidney and heart are also checked, the disease can also cause damage in these organs. The disease is less associated with degenerative changes in the joints of the limbs and the spine. Methods: We report on the progress of a patient with documented family history on alcaptonuria and joint involvement. In the age of 69 the patient got a total hip and knee arthroplasty. Intraoperatively, signs of massive osteoarthritis beside the clinical picture of brown-black synovia were detected. Histopathology confirmed these findings. Results: After arthroplasty of the right hip and both knee joints in 2007 and 2008 the patient is symptom-free. Improvement of the serum and urine levels could be achieved by diet. The remaining joints are not treated surgically yet. Conclusion: In patients with metabolic defects, joints should be checked properly to detect deterioration in an early stage and specifically treated with all available therapies (dietetics, physical therapy, etc.) to delay surgical treatment.
Keywords: alcaptonuria; ochronosis; endoprosthetic replacement; autosomal recessive defect; knee replacement; ddc:610